Monitoramento da dinâmica fluvial em rios não perenes – comportamento de leitos arenosos em ambiente semiárido tropical - Monteiro, Gabriel da Nóbrega (2023)
The river environments in the semi-arid regions are of utmost importance for the occurrence of environmental dynamics and the sustenance of life. Due to the prevailing climatic conditions, water becomes a scarce element, and the capture and conservation of this resource are crucial for the development and maintenance of agricultural activities. In the Brazilian semi-arid regions, hyporheic deposits are responsible for storing a significant amount of water; therefore, alluvial areas serve as the main access points for water in rural regions. Studying the behavior of these environments is essential to ensure proper exploration of this resource and the development of water security for the region. In light of this, the present research aims to analyze the possible hydrogeomorphological responses of non-perennial sandy riverbeds to climatic inputs in the Riacho do Tigre watershed, located in the municipality of São João do Tigre, PB. The study emphasizes the importance of using techniques and equipment capable of analyzing hydrogeomorphological dynamics on both spatial and temporal scales, such as Unmanned Aerial Vehicles (UAVs) and Crest Level. The research also underscores the need for efficient water management tailored to the specificities of each environment, especially in areas prone to degradation.